Fire and explosion at mutual major hazard installations: Review of a case history - Shaluf, I.M.; Ahmadun, F.; Shariff, R.; Mustafa, S.; Said, A.M. (Elsevier Science, 2003)
In industry, it is common that there are independent but related major hazard installations which compliment each other. The link between the major hazard organizations is an interface between the installations. This interface is a critical area for the mutual major hazard installations. Examples of such organizations are chemical cargo ships and their terminal storage yard, the supply vessels and platforms, floating storage tanks at offshore areas and oil tankers, two offshore platforms tied together etc. This paper summarizes the major accident at M. T. Choon Hong III Ship and Tiram Kimia Sdn. Bhd. (TKSB), and also discusses the causes which led to this major accident. It was found that the lack of integrity is the main cause behind the escalation of the fire and explosion at the Choon Hong III Ship and the TKSB. It was noted that the disaster which involved mutual major hazard installation was preceded by two incubation periods.